The answer is

2

P

That’s right.

60^a = 3 60^b = 5 means: a = (log(3))/(2 log(2) + log(3) + log(5)) b = (log(5))/(2 log(2) + log(3) + log(5))

Now, 12^((1-a-b)/(2(1-b)))

2(1-b) = 2(1-(log(5))/(2 log(2) + log(3) + log(5))) = (log(144))/(log(60))

1-a-b = 1-(log(3))/(2 log(2) + log(3) + log(5))-(log(5))/(2 log(2) + log(3) + log(5)) = (log(4))/(log(60))

((log(4))/(log(60)))/((log(144))/(log(60))) = (log(2))/(log(12))

12^((log(2))/(log(12))) = 2

Fill in your details below or click an icon to log in:

You are commenting using your WordPress.com account. ( Log Out / Change )

You are commenting using your Google+ account. ( Log Out / Change )

You are commenting using your Twitter account. ( Log Out / Change )

You are commenting using your Facebook account. ( Log Out / Change )

Connecting to %s

Notify me of new comments via email.

The answer is

2

P

That’s right.

60^a = 3

60^b = 5

means:

a = (log(3))/(2 log(2) + log(3) + log(5))

b = (log(5))/(2 log(2) + log(3) + log(5))

Now, 12^((1-a-b)/(2(1-b)))

2(1-b)

= 2(1-(log(5))/(2 log(2) + log(3) + log(5)))

= (log(144))/(log(60))

1-a-b

= 1-(log(3))/(2 log(2) + log(3) + log(5))-(log(5))/(2 log(2) + log(3) + log(5))

= (log(4))/(log(60))

((log(4))/(log(60)))/((log(144))/(log(60))) = (log(2))/(log(12))

12^((log(2))/(log(12))) = 2